Unlocking dynamics of goal-scoring: the showdown between direct and indirect transition goals across football leagues - Eusebio, Pedro; Prieto-González, Pablo; Marcelino, Rui (Biology of Sport, 2025)
Offensive transitions, (defined as shifts from defense to attack) have an extraordinary impact on goal scoring patterns. Identifying the factors that most significantly influence its achievement is crucial, enabling teams to tailor strategies to their specific characteristics and the particular demands of their championships. The study aims to provide analyzes of the separate and combined impacts of various variables on the success of offensive transitions and their outcomes. The sample comprised 1151 games from nine distinct countries, categorized into three league groups: Top, Marginal, and Emerging. These matches yielded 1649 goals, which were classified as either direct offensive transitions or offensive transitions resulting from positive outcomes (goals scored from set-piece situations following successful offensive transitions). The statistical method employed was binomial logistic regression. A total of 20 to 23% of goals scored by Offensive transitions resulted from positive outcomes. Offensive transitions play a pivotal role in competitive leagues, with 47% of all goals. Top leagues exhibit an even higher proportion (53%) of goals originating from offensive transitions, emphasizing the effectiveness of defensive pressure in specific areas and involving more passes and offensive combinations. All league groups highlighted the central zones of the defensive midfield as essential to initiating successful direct offensive transitions. In Emerging Leagues, they are more likely to succeed with three passes than with two passes. In Marginal leagues, the number of players involved and the passes are related to the starting area. The findings enhance understanding of offensive transition tactics in football for greater scoring impact.